Implementing functional electrical stimulation clinical practice guidelines to support mobility: A stakeholder consultation - Brown, Lisa; Street, Tamsyn; Adonis, Adine; Johnston, Therese E.; Ferrante, Simona; Burridge, Jane H.; Bulley, Catherine (Frontiers in Rehabilitation Sciences, 2023)
Functional Electrical Stimulation (FES) has been used to support mobility for people with upper motor neuron conditions such as stroke and multiple sclerosis for over 25 years. Recent development and publication of clinical practice guidelines (CPGs) provide evidence to guide clinical decision making for application of FES to improve mobility. Understanding key barriers to the implementation of these CPGs is a critical initial step necessary to create tailored knowledge translation strategies. A public involvement and engagement consultation was conducted with international stakeholders including researchers, clinicians and engineers working with FES to inform implementation strategies for CPG use internationally. Reflexive thematic analysis of the consultation transcripts revealed themes including inconsistent use of CPGs, barriers to implementation such as limited access to FES and low clinician confidence, and the need for a tiered education approach with ongoing support. Insights derived from this consultation will inform the development of knowledge translation strategies to support the next steps to implementing FES use for mobility.